Measuring anhedonia: impaired ability to pursue, experience, and learn about reward - Rømer Thomsen, Kristine (Frontiers in Psychology, 2015)
Ribot’s long standing definition of anhedonia as “the inability to experience pleasure” has been challenged recently following progress in affective neuroscience. In particular, accumulating evidence suggests that reward consists of multiple subcomponents of wanting, liking and learning, as initially outlined by Berridge and Robinson, and these processes have been proposed to relate to appetitive, consummatory and satiety phases of a pleasure cycle. Building on this work, we recently proposed to reconceptualize anhedonia as “impairments in the ability to pursue, experience and/or learn about pleasure, which is often, but not always accessible to conscious awareness”. This framework is in line with Treadway and Zald’s proposal to differentiate between motivational and consummatory types of anhedonia, and stresses the need to combine traditional self-report measures with behavioral measures or procedures. In time, this approach may lead to improved clinical assessment and treatment. In line with our reconceptualization, increasing evidence suggests that reward processing deficits are not restricted to impaired hedonic impact in major psychiatric disorders. Successful translations of animal models have led to strong evidence of impairments in the ability to pursue and learn about reward in psychiatric disorders such as major depressive disorder, schizophrenia and addiction. It is of high importance that we continue to systematically target impairments in all phases of reward processing across disorders using behavioral testing in combination with neuroimaging techniques. This in turn has implications for diagnosis and treatment, and is essential for the purposes of identifying the underlying neurobiological mechanisms. Here I review recent progress in the development and application of behavioral procedures that measure subcomponents of anhedonia across relevant patient groups, and discuss methodological caveats as well as implications for assessment and treatment.